Energy-saving scheme supporting ONU modularization with independent-discontinuous transceiving - Yu XIONG; Jian-jun GUAN; Ru-yan WANG (Tongxin xuebao)
To effectively solve the contradiction between energy-saving and packet delay performance in green passive optical network,an energy-saving scheme supporting ONU modularization with independent-discontinuous transceiving is proposed.Utilizing the technology of optical network unit modularization,each module could switch to sleep or awake mode independently and transmit data in specified time slots discontinuously.Simultaneously,to enhance the quality of service of the overall network,the real-time packets are transmitted in the first sub-cycle based on the sub-cycle division strategy.Furthermore,an independent bandwidth allocation algorithm is proposed,which makes the scheme have more advantages in the asymmetric network traffic scenarios.Simulation results verify that the proposed scheme further reduce the network energy consumption on the premise of guarantee the packet delay.